Age and Sex Associations With Body Mass Index in an Audited Postmortem CT Metadata Cohort - Rachmat Hidayat; Muhammad Yoshandi (Sriwijaya Journal of Forensic and Medicolegal, 2025)
Introduction: Open postmortem computed tomography (PMCT) repositories support forensic research, but record duplication and incomplete metadata can distort anthropometric inference. This study examined age- and sex-related variation in body mass index (BMI) after curator-informed audit of VSDFullBody. Methods: We performed a retrospective secondary analysis of 105 metadata rows. A calibration phantom was excluded; seven concordant duplicate pairs were collapsed; both records from four duplicate pairs with conflicting metadata were excluded; curator data reconciled six sex labels and recovered 13 BMI values. The primary cohort comprised 89 decedents, including 83 complete cases. BMI was regressed on age per 10 years and audited biological sex using HC3 standard errors; bootstrap, duplicate-choice, robust-regression, leave-one-out, head-coverage, and missing-outcome sensitivity analyses assessed stability. Results: Mean BMI was 24.2 kg/m2. Each 10-year age increment was associated with 0.49 kg/m2 higher BMI (95% confidence interval [CI], 0.05-0.93; p=0.029). Adjusted BMI was 2.58 kg/m2 higher in male than female decedents (95% CI, 0.18-4.99; p=0.036); the bootstrap 95% CI was 0.34-4.88. Sensitivity estimates retained the same direction. Conclusion: In this audited PMCT metadata cohort, age and male sex were associated with modestly higher BMI. Curator companion files materially increased analyzable completeness, supporting explicit metadata audit before reuse of open forensic imaging collections.